Supporting a Culture of Health in the Workplace: A Review of Evidence-Based Elements. Issue 8 (November 2018) - Flynn, Jennifer Posa; Gascon, Gregg; Doyle, Stephen; Matson Koffman, Dyann M.; Saringer, Colleen; Grossmeier, Jessica; Tivnan, Valeria; Terry, Paul
Objective: To identify and evaluate the evidence base for culture of health elements. Data Source: Multiple databases were systematically searched to identify research studies published between 1990 and 2015 on culture of health elements. Study Inclusion and Exclusion Criteria: Researchers included studies based on the following criteria: (1) conducted in a worksite setting; (2) applied and evaluated 1 or more culture of health elements; and (3) reported 1 or more health or safety factors. Data Extraction: Eleven researchers screened the identified studies with abstraction conducted by a primary and secondary reviewer. Of the 1023 articles identified, 10 research reviews and 95 standard studies were eligible and abstracted. Data Synthesis: Data synthesis focused on research approach and design as well as culture of health elements evaluated. Results: The majority of published studies reviewed were identified as quantitative studies (62), whereas fewer were qualitative (27), research reviews (10), or other study approaches. Three of the most frequently studied culture of health elements were built environment (25), policies and procedures (28), and communications (27). Although all studies included a health or safety factor, not all reported a statistically significant outcome. Conclusions: A considerable number of cross-sectional studies demonstrated significant and salient correlations between culture of health elements and the health and safety of employees, but more research is needed to examine causality.